2019
DOI: 10.1103/physrevd.100.023540
|View full text |Cite
|
Sign up to set email alerts
|

Constraining sterile neutrino cosmology with terrestrial oscillation experiments

Abstract: We explore the complementarity between terrestrial neutrino oscillation experiments and astrophysical/cosmological measurements in probing the existence of sterile neutrinos. We find that upcoming accelerator neutrino experiments will not improve on constraints by the time they are operational, but that reactor experiments can already probe parameter space beyond the reach of Planck. We emphasize the tension between cosmological experiments and reactor antineutrino experiments and enumerate several possibiliti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 145 publications
(197 reference statements)
0
28
0
Order By: Relevance
“…f (y) = [exp(y/w s ) + 1] −1 , where w s ≡ T s a = (T s /T ν ) w and T s /T ν = ∆N 1/4 eff (see e.g. [28,30,31,50,51]). Thus, we show that this latter possibility, denoted as thermal distribution, is inaccurate to study the 3+1 sterile neutrino case, for which we find that the DW approximation is excellent.…”
Section: Momentum Distributions Of the Neutrinosmentioning
confidence: 99%
See 2 more Smart Citations
“…f (y) = [exp(y/w s ) + 1] −1 , where w s ≡ T s a = (T s /T ν ) w and T s /T ν = ∆N 1/4 eff (see e.g. [28,30,31,50,51]). Thus, we show that this latter possibility, denoted as thermal distribution, is inaccurate to study the 3+1 sterile neutrino case, for which we find that the DW approximation is excellent.…”
Section: Momentum Distributions Of the Neutrinosmentioning
confidence: 99%
“…Note that the blue curve is not 4 Since we consider the sterile neutrino in a 3+1 scheme, we restrict ourselves to the case m4 > m3 (normal ordering) or m4 > m2 (inverted ordering), i.e. ∆m 2 41 > ∆m 2 31 2.5 × 10 −3 eV 2 and ∆m 2 41 > ∆m 2 21 7.5 × 10 −5 eV 2 , respectively. Thus, the new squared mass difference does not significantly alter the oscillations of the three active neutrinos.…”
Section: Dependence On the Active-sterile Mixing Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, focusing at CONUS in Ref. [150] it was shown that the complementarity between terrestrial-cosmological experiments may resolve the tension raised by astrophysical observations regarding the existence of sterile neutrinos.…”
Section: E the Existence Of The Sterile Neutrinosmentioning
confidence: 99%
“…[25]). New constraints have been placed on non-standard and generalized interactions [26][27][28][29], nuclear physics parameters [30][31][32], neutrino electromagnetic properties [33,34] and sterile neutrinos [35][36][37]. It has been noted [38][39][40][41][42][43][44][45][46] that light mediators may be accessible to CEνNS experiments, providing information that is complementary to what can be achieved from high-energy and/or precision measurements.…”
Section: Introductionmentioning
confidence: 99%